Pendekatan Pengajaran Guru Bahasa Melayu Sekolah Rendah di Zon Bandar Lahad Datu - Muliana, Tanah (2011)
Learning approach of Malay Language Teacher needs to charge from teacher-centered approach to student-centered approach. A total number of 107 city zone Malay Language teacher in Lahad Datu district from 7 school are choosen as samples for this study. Questionnaires used for data collection. The raw data was analyzed using SPSS for windows version 12.0 software. Descriptive analysis shows that respondent’s background and the teaching approach of primary Malay Language teachers teaching in Lahad Datu district are prone to teacher-centered approach. Other than that, free sample Test-t analysis recorded that there is no significant difference between teacher-centered approach and student-centered approach in term of gender. Meanwhile, ANOVA analysis found out that there is no significant difference in terms of teacher-centered and student-centered approaches by age level. In addition to that, correlation analysis shows insignificantly positive and weak relationship between teaching experiences and teacher-centered approach in Malay Language subject. The same goes to the relationship between teaching experiences and student-centered approach in teaching Malay Language subject which is reported to be insignificantly negative and weak. In a nutshell, primary Malay Language teacher in Lahad Datu District are prone to use teacher-centered approach in their teaching and learning process.